The Influence of Brand Personality, Brand Awareness and Brand Trust on Consumer Loyalty (Case Study on CV. Fajar Tiga Putra) - Fajar Zukhruf Ramadhan; Ahmad Yamin; Junaidi (eCo-Fin, 2024)
Consumer behaviour develops along with technological developments and social factors. This research was conducted to analyse the effect of brand personality, brand awareness and brand trust on consumer loyalty at CV Fajar Tiga Putra, thus creating a strong relationship with their consumers to overcome increasing competition. This research uses quantitative methodology and uses descriptive techniques to analyse the data. The research sample amounted to 100 respondents who were consumers of CV Fajar Tiga Putra who had used products or services from the company. The data were analysed using the Partial Least Square (PLS) method which is included in the Structural Equation Modelling (SEM) domain. Research findings indicate that brand personality, brand awareness, and brand trust have a positive and significant impact on consumer loyalty towards CV. Fajar Tiga Putra. This means that the better the brand personality, brand awareness, and brand trust established by CV. Fajar Tiga Putra, the higher the consumer loyalty towards CV. Fajar Tiga Putra's products. Additionally, brand personality, brand awareness, and brand trust are able to simultaneously influence consumer loyalty towards CV. Fajar Tiga Putra. The conclusion in this study is that the presence of brand personality, brand awareness and brand trust through positive interactions with consumers increases long-term loyalty. It also facilitates the purchase decision-making process, makes the brand more desirable, and fosters emotional connectivity, which encourages consumer loyalty.